(untitled) (Mustansiria Dental Journal, 2024)
The temporomandibular joint disorders are defined as a collective term embracing a number of clinical problems that involve the masticatory muscles, the TMJ and associated structures. Myofacial pain dysfunction syndrome (MPDS) is the most common .functional disorder of TMJ Many etiological factors have been blamed to produce pain and dysfunction of .TMJ such as stress, malocclusion and parafunctional habits Stress is thought to be responsible for hyperactivity of the muscles of mastication .which leads to muscle fatigue then muscle spasm and pain The purpose of this study was to determine the role of stress as an ctiological .)factor in (MPDS One hundred dental students were used in this study and evaluated for having MPDS. Another sample of one hundred persons from the general population were .evaluated in the same manner to be used as control The results of this study indicated that (55%) of participating students have MPDS) because of the great amotmts of stress they are going through. While in control group there was only (7%).